The The Relationship Between Infant Birth Weight, Gestational Age, and Hyperbilirubinemia Incidence in Neonates - Steve, Cornelius; Hidayah , Dwi; Nugroho , Irfan Dzakir; Putra, Andhika Trisna (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Neonatal hyperbilirubinemia is an occurrence where a serum bilirubin value of 5-10mg/dL is obtained and is characterized by jaundice in newborns. This occurrence can be influenced by several factors, one of which is the birth weight of the baby <2,500 grams which is called Low Birth Weight (LBW). The incidence of LBW can be influenced by maternal age, infections that occurred before pregnancy, and one of them is gestational age LBW it self is one of the most critical health problems in various countries. Therefore, researchers are interested in finding the relationship between infant birth weight and gestational age with the incidence of neonatal jaundice. Subjects and Method: This was a cross-sectional study conducted in Rumah Sakit Umum Daerah Dr. Moewardi on Surakarta. The subjects of this study were 89 neonates who were included in the criteria. The population of this study were neonates with hyperbilirubinemia. Sampling was carried out retrospectively using patient medical records from January to December 2021, using purposive sampling technique. The dependent variable was incidence of hyperbilirubinemia. The independent variables were low birth weight and gestational age. The data were then processed using SPSS version 26 and analyzed using the chi-square test. Results: LBW and preterm increased the incidence of neonatal hyperbilirubinemia in neonates. Infants with LBW increased neonatal hyperbilirubinemia by 2.34 times compared to adequate birth weight, and this result was statistically significant (OR = 2.34; 95% CI = 1.58 to 3.47; p<0.001). Preterm infants increased neonatal hyperbilirubinemia by 2.55 times compared to term, and this result was statistically significant (OR = 2.55; 95% CI = 1.68 to 3.58; p <0.001). Conclusion: There is an important correlation between infant birth weight and gestational age with the incidence of hyperbilirubinemia in neonates in the perinatology room at Rumah Sakit Umum Daerah Dr. Moewardi, Surakarta.